2019
DOI: 10.1016/j.ebiom.2019.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Systematic cancer-testis gene expression analysis identified CDCA5 as a potential therapeutic target in esophageal squamous cell carcinoma

Abstract: Background Esophageal squamous cell carcinoma (ESCC) is one of the most lethal malignancies with poor prognosis. Cancer-testis genes (CTGs) have been vigorously pursued as targets for cancer immunotherapy, but the expressive patterns and functional roles of CTGs remain unclear in ESCC. Methods A systematic screening strategy was adopted to screen CTGs in ESCC by integrating multiple public databases and RNA expression microarray data from 119 ESCC subjects. For the newl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 61 publications
3
36
0
Order By: Relevance
“… 46 Furthermore, several studies found that CT genes play fundamental roles in the cell cycle pathway in tumorigenesis. 20 , 47 In line with this, in our present analysis, CT gene in HCC was found mainly involves in the regulation of cell cycle, intriguingly both in mitotic and in meiotic, which is essential for tumorigenesis. This is consistent with the fact that CT gene is highly testicular and cancer-specific, making it a promising candidate molecular-targeted therapies for HCC.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“… 46 Furthermore, several studies found that CT genes play fundamental roles in the cell cycle pathway in tumorigenesis. 20 , 47 In line with this, in our present analysis, CT gene in HCC was found mainly involves in the regulation of cell cycle, intriguingly both in mitotic and in meiotic, which is essential for tumorigenesis. This is consistent with the fact that CT gene is highly testicular and cancer-specific, making it a promising candidate molecular-targeted therapies for HCC.…”
Section: Discussionsupporting
confidence: 83%
“…Prognostic values of CT genes were reported in many tumor types, such as multiple myeloma, 53 clear cell renal cell carcinoma, 54 testicular germ cell tumor, 55 and esophageal squamous cell carcinoma. 47 In our study, survival analysis revealed that 9 CT genes of our identified hub CT genes were associated with the poor survival of HCC, which makes them promising candidate prognostic biomarkers for HCC. These findings lead to a possibility that these CT gene products might have a functional role in the pathogenesis of cancer resulting in a bad evolution.…”
Section: Discussionmentioning
confidence: 63%
“…In addition, it has also been con rmed that CDCA5 was signi cantly upregulated in breast cancer, bladder cancer, oral squamous cell cancer, urinary tract carcinoma, head and neck squamous cell carcinoma, and esophageal squamous cell carcinoma, and the high expression of CDCA5 was closely related to pathological stages and poor prognosis of patients [21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 96%
“…In order to explore the specific mechanism of the effect of these genes on survival, we screened the top 10 genes (CDC20, NCAPH, CDCA5, BUB1, CDCA8, PBK, KIF2C, TPX2, TTK and TOP2A). By retrieving related literature, we found that CDCA5 and CDCA8, as important regulatory proteins in the cell cycle in cancer, were recognized as oncogenes [26][27][28][29]. However, compared with other genes, there scarcely no reports about the mechanism of CDCA5 and CDCA8 with GBM.…”
Section: Discussionmentioning
confidence: 99%